2019
DOI: 10.1111/jace.16759
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dielectric properties of temperature‐stable zircon‐type (Bi, Ce)VO4 solid solution ceramics

Abstract: In the (Bi1 − xCex)VO4 (0 ≤ x ≤ 1) system, we found that the (Bi1 − xCex)VO4 (0 ≤ x ≤ 0.1) belongs to the monoclinic scheelite phase and the (Bi1 − xCex)VO4 (0.7 ≤ x ≤ 1) belongs to the tetragonal zircon phase, while the (Bi1 − xCex)VO4 (0.1 < x < 0.7) belongs to the mixed phases of both monoclinic scheelite and tetragonal zircon structure. Interestingly, two components with near‐zero temperature coefficient of resonant frequency (TCF) appeared in this system. In our previous work, a near‐zero TCF of ~+15 ppm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Generally, τ f values are determined by the temperature coefficient of the dielectric constant (τ ε ) in the single-phase area, and τ ε was calculated using Formulas (14) and (15). [30][31][32][33] where α is a constant of about 10 ppm/°C for ceramics, α m and V represent the polarizability and volume, respectively. Hence, τ f values depend mainly on τ ε .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, τ f values are determined by the temperature coefficient of the dielectric constant (τ ε ) in the single-phase area, and τ ε was calculated using Formulas (14) and (15). [30][31][32][33] where α is a constant of about 10 ppm/°C for ceramics, α m and V represent the polarizability and volume, respectively. Hence, τ f values depend mainly on τ ε .…”
Section: Resultsmentioning
confidence: 99%
“…Zhou Di et al reported that the sum of the second and third terms in the square brackets of Formula (15) is a constant (approximately 6 ppm/°C) and that τ ε values are primarily controlled by the first terms (approximately -1 ~ -10 ppm/°C), which represent the direct dependence of polarizability on temperature. 32 Therefore, τ ε is determined by crystal structure, such as restoring forces acting on the ions, 34 and restoring forces are positively related to octahedral distortions. 35 The τ f values of Ca 1−x Sr x SnSiO 5 (0 ≤ x ≤ 0.15) ceramics could be attributed to the SnO 6 octahedral distortion.…”
Section: Resultsmentioning
confidence: 99%
“…Wireless communication is largely furthered by 5G technologies with decades of development. Microwave dielectric ceramics have been widely applied in wireless communication systems, such as dielectric resonator, filter, duplexers, and antenna 1‐3 . For 5G wireless communication, high transmission speed (low latency) for devices is more important than miniaturization 4‐6 .…”
Section: Introductionmentioning
confidence: 99%
“…Microwave dielectric ceramics have sprung up in the communication industry and received widely attention. It is required to have a high quality factor (Q×f), a moderate dielectric constant (εr) and a near-zero temperature coefficient of resonant frequency (τf) to meet the demands of application [1][2][3][4]. Recently, researchers focused on novel microwave dielectric ceramics [5][6][7].…”
Section: Introductionmentioning
confidence: 99%